2010
DOI: 10.1371/journal.ppat.1000912
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmodium falciparum-Specific Human Memory B Cell Compartment Expands Gradually with Repeated Malaria Infections

Abstract: Immunity to Plasmodium falciparum (Pf) malaria is only acquired after years of repeated infections and wanes rapidly without ongoing parasite exposure. Antibodies are central to malaria immunity, yet little is known about the B-cell biology that underlies the inefficient acquisition of Pf-specific humoral immunity. This year-long prospective study in Mali of 185 individuals aged 2 to 25 years shows that Pf-specific memory B-cells and antibodies are acquired gradually in a stepwise fashion over years of repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
245
2
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 207 publications
(281 citation statements)
references
References 71 publications
(94 reference statements)
29
245
2
4
Order By: Relevance
“…This occurs in a cGAS-independent manner late after initial priming and expansion and occurs in conjunction with a reduction in the number of GC B cells. Since plasmablasts are thought to be short lived and not contribute to the memory pool (85), our data support epidemiologic observations that high levels of ongoing parasite transmission are associated with poor-quality, short-lived B cell responses (86)(87)(88). In contrast to the reduced number of MSP1-specific B cells, we determined that ongoing infection had no effects on the total number of endogenous antigen-specific CD4 + T cells but did affect the formation of GC Tfh CD4 + T cells.…”
Section: Discussionsupporting
confidence: 82%
“…This occurs in a cGAS-independent manner late after initial priming and expansion and occurs in conjunction with a reduction in the number of GC B cells. Since plasmablasts are thought to be short lived and not contribute to the memory pool (85), our data support epidemiologic observations that high levels of ongoing parasite transmission are associated with poor-quality, short-lived B cell responses (86)(87)(88). In contrast to the reduced number of MSP1-specific B cells, we determined that ongoing infection had no effects on the total number of endogenous antigen-specific CD4 + T cells but did affect the formation of GC Tfh CD4 + T cells.…”
Section: Discussionsupporting
confidence: 82%
“…Functional characterization of VAR2CSA-reactive antibodies in men, children, and nulligravidae might shed light on this issue. The other point relates to previous reports that intensive and/or repeated antigen exposure to malaria antigens can drive expansion of so-called "atypical" memory B cells (14) that may be functionally "exhausted" (13,74,75), as has been observed in HIV infection (76). It has been suggested that this could explain the paradoxical inverse relationship between parasite exposure and acquired immunity observed in some studies (58,59).…”
Section: Discussionmentioning
confidence: 81%
“…In addition, correlations were only observed between small proportions (24 of 648) of all pairs of antibody levels,73 strongly suggesting that naturally acquired immunity to a large array of antigens may not be co‐acquired. These results are also buttressed by independent experiments where the extent of correlation between antibody levels in a healthy state and during concurrent infection seemed to be antigen‐specific 43, 77. Polymorphic GPI‐anchored antigens [such as anti‐mitochondrial antibodies (AMA)‐1] often induced relatively higher antibody levels compared with conserved antigens (such as the Rhs) 43, 78, 79, 80.…”
Section: Antibodies and Protection: What We Have Learnt So Farmentioning
confidence: 99%